Philosophy Of Language In Contemporary Master’s Theses : A Philosophical Exploration - Sihite, Meida Rabia; Manihuruk, Leonita Maria Efipanias; Marpaung, Agus Salim; Ginting, Siti Aisyah; Sari, Winda Setia (LPPM Universitas PGRI Sumatera Barat, 2023)
This study examines the philosophy of language as presented in contemporary master's theses, focusing on the realms of ontology, axiology, and epistemology. The background of the study acknowledges the importance of philosophical inquiry at the master's level and its role in advancing language philosophy. The research objectives are to examine and to categorize the specific domains of the philosophy of language within selected theses, aiming to understand the scope and diversity of discussions in these areas. Employing content analysis and comparative analysis as research methods, the study comprehensively analyzes five master's theses from various disciplines. The technique for data analysis involves a detailed examination of the theses to identify the prevalence and treatment of the three philosophical domains. Research findings reveal a rich tapestry of perspectives on ontology, axiology, and epistemology, each thesis contributing uniquely to the field. The conclusion highlights the complexity and diverse nature of contemporary language philosophy. This study serves as evidence to the varied and intricate discussions shaping the philosophy of language today.